Probing cell–matrix interactions in RGD-decorated macroporous poly (ethylene glycol) hydrogels for 3D chondrocyte culture. (24th June 2015) - Zhang, Jingjing; Mujeeb, Ayeesha; Du, Yanan; Lin, Jianhao; Ge, Zigang
Abstract: Macroporous hydrogels have shown great promise as scaffolds for cartilage engineering by facilitating nutrition transport and tissue in growth. Cell–matrix adhesion—a fundamental process in tissue engineering—has shown a profound effect on subsequent cell phenotype, extracellular matrix (ECM) accumulation, and tissue reorganization. In this study, arginine-glycine-aspartic acid (RGD) was introduced to macroporous hydrogels of poly (ethylene glycol) (PEG) to fabricate PEG-G400 (with 0.4mM RGD) and PEG-G2000 (2mM RGD) to probe the cell–matrix interactions within hydrogels. Primary chondrocytes demonstrated a slightly stretched morphology with increasing RGD concentration and PEG-G2000 hydrogels boosted cell viability, proliferation, and deposition of collagen II and GAG, in comparison to the PEG-G400 and PEG-RED groups. Results also revealed chondrocytes within the cell aggregates underwent dedifferentiation and hypertrophy within RGD incorporated hydrogels, as evidenced by the high level of gene expression of collagen I on day 14 and strong immunohistological staining of collagen X and collagen I on day 35. Evidently, a high concentration of RGD (2mM RGD) enhanced cell–matrix interactions through elevating the expression of integrin β 1 and vinculin. Thus, the integration of RGD in macroporous hydrogels with a concentration of 2 mM may be sufficient for improving cell functionality, with a slight probability of dedifferentiation and hypertrophy of chondrocytes.